X-ray powder diffraction data for tetrazene nitrate monohydrate, C2H9N11O4 - Ryšavý, Jan; Maixner, Jaroslav (My University, 2021)
X-ray powder diffraction data, unit-cell parameters, and space group for tetrazene nitrate monohydrate, C2H9N11O4, are reported [a = 5.205(1) Å, b = 13.932(3) Å, c = 14.196(4) Å, β = 97.826(3)°, unit-cell volume V = 1019.8(4) Å3, Z = 4, and space group P21/c]. All measured lines were indexed and are consistent with the P21/c space group. No detectable impurities were observed.
Data RTG práškové difrakce monohydrátu dusičnanu tetrazenu, C2H9N11O4
Keywords: X-ray powder diffraction; tetrazene; hydrate; explosive; munitions industry; RTG prášková difrakce; tetrazen; hydrát; výbušina; zbrojní průmysl